Health Dimensions of COVID-19 in India and Beyond 2022
DOI: 10.1007/978-981-16-7385-6_13
|View full text |Cite|
|
Sign up to set email alerts
|

Financing for a Resilient Health System in India: Lessons from the COVID Pandemic

Abstract: COVID-19 has again brought into focus the need for building a resilient health system which can cater efficiently and equitably to the population during normal times as well as during unforeseen events like an epidemic, pandemic, or other unanticipated occurrences that impact human health. To be prepared well in advance means to avoid unnecessary morbidity and mortality on the one hand, and minimize socio-economic impact on individuals and households, on the other. The author argues that each component that go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Healthcare delivery in India is characterised by a mix of public and private sectors. Although public healthcare is provided free of cost to the people, due to various deficiencies at the public healthcare facilities, many families seek healthcare from the private sector, incurring out-of-pocket expenditure (Common Health Fund, 2020; Gupta, 2022).…”
Section: Health Systems—india Vs Ksamentioning
confidence: 99%
“…Healthcare delivery in India is characterised by a mix of public and private sectors. Although public healthcare is provided free of cost to the people, due to various deficiencies at the public healthcare facilities, many families seek healthcare from the private sector, incurring out-of-pocket expenditure (Common Health Fund, 2020; Gupta, 2022).…”
Section: Health Systems—india Vs Ksamentioning
confidence: 99%
“…Marginean and Orastean [41] examined, during COVID-19 crisis in the European Union, the relationship between health financing and pandemic preparedness. They found that high health spenders performed better in facing the COVID-19 crisis and that high financing increases performance and resilience of health systems [42] . Ovsiannikova [43] found that higher health expenditure reduced COVID-19 mortality in low-income countries but the effect of health expenditure on mortality was insignificant in middle- and high-income countries.…”
Section: Introductionmentioning
confidence: 99%